Leveraging Artificial Intelligence for Enhanced Administrators Decision Making in Educational Institutions: A Comprehensive Exploration of Applications, Challenges, and Opportunities - Okokoyo, Isabella Ezinwa; Nwaham, Caroline Obioma; Nwachukwu, Ogochukwu Gloria (NIU Journal of Educational Research, 2024)
The role of Artificial Intelligence (AI) as a powerful tool for enhancing decision-making in educational institutions has been examined. This paper provides a detailed insight into the exploration of the applications, challenges, and opportunities inherent with leveraging AI for improved decision-making in educational institutions. The paper draws on existing research and current trends, to examine the different applications of AI in education. This includes but not limited to personalized learning, predictive analytics, and administrative optimization. The challenges and ethical considerations associated with the use of AI adoption, such as algorithmic bias, data privacy, and transparency were highlighted. Despite these challenges, the paper identifies numerous opportunities for educational stakeholders to harness the transformative potential of AI to improve teaching, learning, and administrative processes. Recommendations are provided for policymakers, educators, and stakeholders to adopt AI as a catalyst for innovation and enhanced educational decision-making. The paper concluded that by prioritizing responsible AI use, through fostering interdisciplinary collaboration, promoting equity and inclusion, educational institutions can open the doors to the full benefits of the transformative potentials of AI to improve decision-making and foster educational equity.